PENGARUH PEMBINAAN PENILIK DAN MOTIVASI KERJA GURU TERHADAP KINERJA MENGAJAR GURU PENDIDIKAN ANAK USIA DINI (PAUD) DI KECAMATAN BANJARAN KABUPATEN BANDUNG - Arief Syauqi Muhammad, - (2019)
Tujuan penelitian adalah mendeskripsikan kinerja mengajar guru, pembinaan penilik dan motivasi kerja guru serta menghitung pengaruh pembinaan penilik dan motivasi kerja terhadap kinerja mengajar guru PAUD di Kecamatan Banjaran Kabupaten Bandung. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Pengumpulan data menggunakan observasi, kuisioner, dan dokumentasi, sedangkan teknik analisis data menggunakan uji koefisien korelasi, regresi dan koefisien determinasi. Objek pada penelitian ini adalah guru PAUD di Kecamatan Banjaran Kabupaten Bandung dengan jumlah sampel 68 responden. Hasil penelitian menunjukan bahwa pembinaan penilik dan motivasi kerja berpengaruh secara positif dan signifikan terhadap kinerja mengajar guru PAUD di Kecamatan Banjaran Kabupaten Bandung.;--The phenomenon of research that took place in Banjaran District, Bandung Regency was that the PAUD teacher's performance was not optimal which could be caused by the lack of optimal guidance and motivation of teachers who were not good enough. The purpose of this study was to describe the teaching performance of PAUD teachers, coaching by the supervisor and work motivation of the teacher as well as calculating the influence of guidance by the supervisor and work motivation on the teaching performance of PAUD teachers in Banjaran District, Bandung Regency. The method used in this study is descriptive quantitative. Data collection uses observation, questionnaires, and documentation, while data analysis techniques use the correlation coefficient test, regression test and coefficient of determination. The Paud teacher who was the object of this study was PAUD teachers in Banjaran District, Bandung Regency with a total sample of 68 respondents. The results showed that coaching by the supervisor and work motivation had a positive and significant effect on the teaching performance of PAUD teachers in Banjaran District, Bandung Regency. Based on the calculation of the magnitude of the influence of guidance by the supervisor on the teaching performance of PAUD teachers in Banjaran District, Bandung Regency is 29.6%, then the magnitude of the effect of work motivation on teacher teaching performance is 33.0%, and the last is the influence of supervisors and work motivation on the teaching performance of PAUD teachers in Banjaran Kabupaten District, Bandung was 43.6%. Based on the results of the calculation of the variables of motivation, it gives a greater influence on the teaching performance of the teacher compared to the guidance by the teacher. Based on this, the researcher recommends that guidance by inspectors be more often carried out and with the implementation of systematically arranged and breastfeeding and having concrete goals and more time duration.